THE IMPORTANCE OF TOUR GUIDES IN CULTURAL TOURISM - Ulmasova Bakhora Asrorovna (International Journal of Literature and Language Studies, 2026)
Cultural tourism has emerged as one of the fastest-growing segments of the global travel industry, driven by an increasing desire among travellers to engage authentically with the history, traditions, and living cultures of destinations they visit. At the centre of this experience stands the tour guide — a professional whose role extends far beyond logistical coordination. This article examines the multifaceted importance of tour guides in cultural tourism, exploring their functions as cultural interpreters, economic contributors, heritage ambassadors, and community liaisons. Drawing on established frameworks in tourism management, the article presents key arguments for elevating the professional status of tour guides, provides actionable recommendations for industry stakeholders, and outlines an implementation roadmap for sustainable improvement. The findings affirm that tour guides are not peripheral service providers but indispensable pillars of a meaningful and responsible cultural tourism ecosystem.